Diversity, density and distribution of mangrove crabs in cochin backwaters - Akshaya Vijayan (KUFOS, 2019)
Healthy mangrove forests provide a critical habitat for many speciesfauna. Mangroves serves as the most suitable feeding, breeding and nursery grounds for crabs and other crustaceans is under various anthropogenic threats. In this prelude an investigation on the density and diversity of Brachyuran crabs in three selected mangrove patches of Cochin backwaters, namely Puthuvyppu, Panangad and Mulavukad are carried out for a period of one year( May 2018 -April 2019). A total of 14 species of brachyuran crabs were recorded belonging to 10 genera and 5 families in such a way that maximum species diversity was recorded in Puthuvyppu; whereas panangad and Mulavukad recorded 12 species each. The qualitative and quantitative estimation of brachyuran crabs and their relation to water quality and sediment characteristics were also evaluated to recognize the most influencing variables of water and sediments that effects on crab diversity. The co-relation matrix proved that salinity and water temperature played a significant relation with that of crab diversity. The percentage wise species composition of brachyuran crabs against various seasons and stations were worked out separately. The univariate methods of biodiversity indices were analysed season wise for the three stations. Multivariate analysis such as cluster and MDS were portrayed for the month wise ordination in different stations. The results obtained stand as a base line ready reference for work of this kind in future for unraveling the crab density and diversity.